THE EFFECT OF SUPPLEMENTATION GARLIC OIL AS AN ANTIBACTERIAL ACTIVITY AND SALTING TIME ON THE CHARACTERISTICS OF SALTED EGG - Putri Widyanti Harlina; Ma Mei Hu; A M Legowo; Y B Pramono (Jurnal Aplikasi Teknologi Pangan, 2012)
This study has been done to examine the influences of garlic oil, salting time in the characteristics of salted egg. Typical bacterial used in this study were Escherichia coli, Salmonella enteritidis, and Staphylococcus aureus. They were obtained from the culture collection of National R&D Center for Egg Processing Laboratory, Food Science and Technology College, Huazhong Agricultural University, Wuhan, China. The experimental design was completely randomized design with factorial factor A x B (3 x 5) for three replications. Factor A were supplementation of garlic oil with different concentration (0%; 0.1%; 0.5%) and factor B were different time for salting process (0; 7; 14; 21; 28 days). The research was done through several activities, the determination of garlic oil as an antibacterial activity and making salted eggs in the presence of garlic oil are performed.  The results showed that garlic oil had antibacterial activity on the three bacteria used in this study. The minimum inhibitory concentration (MIC) of garlic oil was used as a determination of the concentration in salted egg presence of garlic oil. Egg white and yolk of duck eggs with different salting time and concentration of garlic oil showed slight differences in chemical composition and textural properties as salting proceeded. Both of treatment could induce solidiﬁcation of yolk accompanied by oil exudation and the development of gritty texture. Thus both of treatment somehow affected the characteristics of the resulting egg white and egg yolk.